The intonation of Spanish spoken in Bucaramanga (Colombia) - Yeimy J. Roberto (Estudios de Fonética Experimental, 2023)
This paper presents the characteristics of the intonation of Spanish spoken in Bucaramanga, Colombia, a variety considered as “strong and rude”. Spontaneous, semi-spontaneous and read utterances from four participants were analysed acoustically. After stylisation with MOMEL, the data was tagged according to the Sp_ToBI system, within the Autosegmental-Metrical model. The declarative, interrogative, and exhortative contours were compared with the intonational inventories available for Spanish. The results confirm prior dialectal boundaries based on lexical data and supports the dichotomy between coastal and mountain varieties in the dialects of Spanish spoken in Colombia.